The melancholy of a political documentarist. Issue 3 (2nd September 2019) - Chanan, Michael
ABSTRACT: Exploring the conditions and desire for political documentary at the present conjuncture, drawing on the author's experience as a London-based freelance documentarist since the 1970s and especially, since the turn of the millennium, making documentaries from a base within academia.